THE EFFECT OF USING INFORMATION TECHNOLOGIES IN TEACHING LITERACY TO YOUNG STUDENTS (Scientific journal of the Fergana State University, 2024)
The article is about the development of scientific-methodical foundations of teaching using information technologies and multimedia tools during the period of preparing young students for literacy. In the world, special attention is being paid to improving the quality and efficiency of education, using the possibilities of modern pedagogical and information technologies, based on the competence approach to the educational process. In teaching, it is important to develop creative abilities and improve students' theoretical, methodological and methodological foundations through the effective use of computer pedagogical software tools, informational educational environments. At the international level, scientific and research work aimed at improving the mechanisms of implementing innovative technologies, didactic materials and information technologies based on the principles of modern development is being carried out to improve the quality and efficiency of education. The results of the research serve to strengthen the theoretical foundations of science based on the formation of necessary competences related to science in young children, revealing the essence of interdisciplinary dependence, integration of educational technologies with information technology tools. Measures aimed at creating an additional learning environment for young students by modernizing the educational process of our country's comprehensive schools and strengthening the material and technical base will bring the spiritual, moral and intellectual development of the young generation to a qualitatively new level. it is required to raise the innovative forms and methods of education in the educational process, to form a strong motivation to learn in students through an integrated learning environment based on information technologies.